الجريمة السياسية ومفهومها في الشريعة الإسلامية والقانون الوضعي الليبي Political crime and its conceptualization in the Islamic law and the Libyan positive law - Hasanulddin, Mohd; Abdel Karem Abdel Rahem, Abdel Karem (2019)
The topics of political crimes, its research and implementation are important and significant topics in light of the continuation of the ruling based on the perspectives of the Islamic law (Shariah) as well as the positive law in terms of legalizations and adaptations of this important matter. Moreover, there is no doubt that it would be useful to compare the various perspectives on this matter so as to identify the similarities and the differences between the ruling of Shariah and ruling of positive law. Here lies the research problem. This research aims to clarify the meaning of political crime and its concept in the various views of the Islamic law and the positive Libyan law. The researcher follows the methods of inductive, descriptive, and comparative approach, seeking to achieve the research objectives and to answer the research questions related to the many issues and provisions in regard to political crime from the perspectives of the Islamic law and the provisions of the Libyan Penal Code. The research findings suggest that the concept of political crime is defined as: the criminal act that collides with the political system of a state, from the outside as the independence of the state and territorial sovereignty and its relationship with other states which are classified in the Islamic law into crimes of opinion, actual crimes and those have no penalty for the freedom of opinion and expression. The concept of internal political crimes is those that affected the internal sovereignty of a state, including constitutional rights, other crimes against the form of government and the organization of public authorities and constitutional institutions.